Cholinergic signaling inhibits oxalate transport by human intestinal T84 cells - Hassan, Hatim A. (American Physiological Society, 2012)
Urolithiasis remains a very common disease in Western countries. Seventy to eighty percent of kidney stones are composed of calcium oxalate, and minor changes in urinary oxalate affect stone risk. Intestinal oxalate secretion mediated by anion exchanger SLC26A6 plays a major constitutive role in limiting net absorption of ingested oxalate, thereby preventing hyperoxaluria and calcium oxalate urolithiasis. Using the relatively selective PKC-δ inhibitor rottlerin, we had previously found that PKC-δ activation inhibits Slc26a6 activity in mouse duodenal tissue. To identify a model system to study physiologic agonists upstream of PKC-δ, we characterized the human intestinal cell line T84. Knockdown studies demonstrated that endogenous SLC26A6 mediates most of the oxalate transport by T84 cells. Cholinergic stimulation with carbachol modulates intestinal ion transport through signaling pathways including PKC activation. We therefore examined whether carbachol affects oxalate transport in T84 cells. We found that carbachol significantly inhibited oxalate transport by T84 cells, an effect blocked by rottlerin. Carbachol also led to significant translocation of PKC-δ from the cytosol to the membrane of T84 cells. Using pharmacological inhibitors, we observed that carbachol inhibits oxalate transport through the M(3) muscarinic receptor and phospholipase C. Utilizing the Src inhibitor PP2 and phosphorylation studies, we found that the observed regulation downstream of PKC-δ is partially mediated by c-Src. Biotinylation studies revealed that carbachol inhibits oxalate transport by reducing SLC26A6 surface expression. We conclude that carbachol negatively regulates oxalate transport by reducing SLC26A6 surface expression in T84 cells through signaling pathways including the M(3) muscarinic receptor, phospholipase C, PKC-δ, and c-Src.